Online Learning Strategy for Islamic Education Studies during the Covid-19 Pandemic in Elementary Schools - Dahmayati Dahmayati; Syamsu Sanusi; Kartini Kartini (State Islamic Institute of Palopo, 2021)
The purpose of this study is to describe the learning strategy of Islamic Religious Education during the COVID-19 pandemic, explain the implementation of online learning of Islamic Religious Education during the Covid-19 period. This research is qualitative research that uses a pedagogical approach. The subjects of this study consisted of the head of the foundation, principal, students, parents, staff at the Integrated Islamic Elementary School Insan Rabbani, Malili District, East Luwu Regency. Data analysis in this study starts from data collection, data reduction, data presentation, and concluding. The results showed that the learning strategies implemented at SD Islam Terpadu Insan Rabbani were expository, inquiry, contextual, and comparative learning strategies. The learning model implemented is a Self Organized Learning Environment (sole) model and Project-Based Learning. The implementation of online PAI learning at the school uses the zoom application, google meet, classroom, and WhatsApp with lecture and demonstration methods.